Ovarian cancer prevention and screening – where do we stand today? - Cristina Bucur; Irina Balescu; Sorin Petrea; Bogdan Gaspar; Lucian Pop; Valentin Varlas; Adrian Hasegan; Marilena Stoian; Gabriel Petre Gorecki; Nicolae Bacalbasa (Journal of Mind and Medical Sciences)
Widely recognized as the most deathful gynecologic malignancy affecting women worldwide, ovarian cancer has reported a significant decline in terms of prevalence and incidence in the last decades. This fact has been especially explained by to the use of menopausal hormonal therapy and of oral contraceptives in association with genetic, oncologic and gynecologic counseling. The aim of the current review is to discuss about actual ovarian cancer prevention and screening tools. For this reason, we reviewed several data related to ovarian cancer, such as: incidence and risk factors, histopathological types (epithelial with high- and low-grade serous carcinomas, clear cell carcinoma, mucinous carcinoma, germ cells ovarian cancer tumors), as well as screening, diagnosis and prevention methods (ovulation disruption, surgical prevention, etc.). Although progress has been reported in the last decades in terms of early diagnosis and treatment of ovarian cancer, this malignancy still represents a significant health problem affecting women worldwide. However, it seems that the golden key for optimizing the long-term outcomes in such patients is represented by a better understanding of the complex pathogenesis of this disease.